Efecto de la actividad física sobre la calidad de vida de personas con fibromialgia (2015)
Introduction: There is evidence of the positive effects of physical activity in fibromyalgia; however, in Medellín are scarce investigations had evaluated its effects on quality of life. Objective: To compare the profile of quality of life in sedentary patients with fibromyalgia and a group of patients with an adequate physical activity pattern from Medellin. Methods: Cross-sectional analytical study on 71 people sedentary and 29 with a suitable pattern of physical activity assessed through the questionnaire IPAQ who attended consultation with a rheumatologist in an institution providing specialized health services, all diagnosed with fibromyalgia according to the criteria of the American College of Rheumatology. One analysis was performed using chi square test to ensure uniformity in socio-demographic and clinical characteristics of the study groups. The dimensions of quality of life MOSSF-36 WHOQOL-BREF and the FIQ were measured; they were compared in the two study groups with the Mann Whitney U test. Quantification of the confusion was performed with linear regression. Results: No statistical differences were found in the characterization of the study groups (p >0.05), both were made up a higher proportion of women, adult medium, low education social status, low income, overweight or obesity, use of antidepressants and comorbidities. Seven of the eight dimensions of MOSSF-36 showed statistically better results in patients who are physically active (p < 0.05): physical function (46.4 vs 35.4) physical performance (26.7 vs 12.7), bodily pain (35.2 vs 23.9), general health (51.1 vs 38.3), vitality (47.9 vs 33.8), social function (62.9 vs 49.6) and emotional function (37.9 vs 17.8); Likewise best results were found for the dimensions of work, fatigue, morning tiredness, feeling good and the overall result of the FIQ and physical health of the WHOQOL-BREF. The social participation was found associated with better quality of life related to health. Conclusion: Physical activity and social participation improve the profile of quality of life of patients with fibromyalgia, both in its physical as psychosocial dimensions, this increasing evidence of the need to address strategies unconventional but complementary to traditionally applied intervention. © iMedPub.